Preventing identity theft in your business : how to protect your business, customers, and employees - Collins, Judith M. (John Wiley, 2005)
"Preventing Identity Theft in Your Business is the first book to address identity fraud from the business perspective. It helps employee-manager teams develop a set of security standards using step-by-step instructions written in plain, easy-to-understand language. Identity theft expert Judith Collins offers practical guidance on how to spot identity theft, as well as how to prevent it from ever occurring. Using techniques culled from industrial and organizational psychology, the management sciences, and the field of criminal justice, the methods covered here are inexpensive, comprehensive, and universally applicable to all business, regardless of size, type, or geographic location."--Jacket